2013
DOI: 10.1002/pd.4087
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum placental growth factor and α‐fetoprotein testing in first trimester screening for Down syndrome

Abstract: Results suggest a substantial benefit of adding PlGF to the combined test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 16 publications
4
32
0
Order By: Relevance
“…The results for trisomy 21 in combined screening with the addition of PLGF and AFP are compatible with the prediction from previous prospective and retrospective case control studies [5,6,15]. This study has shown that measurement of PLGF and AFP is also useful in screening for trisomies 18 and 13.…”
Section: Discussionsupporting
confidence: 78%
“…The results for trisomy 21 in combined screening with the addition of PLGF and AFP are compatible with the prediction from previous prospective and retrospective case control studies [5,6,15]. This study has shown that measurement of PLGF and AFP is also useful in screening for trisomies 18 and 13.…”
Section: Discussionsupporting
confidence: 78%
“…Statistical modeling predicted the detection rate for a fixed false‐positive rate when PlGF, AFP or both are used in a serum‐only screening test in combination with existing markers, PAPP‐A and free β‐hCG. Donalson et al . also used modeling to investigate these combinations and reached the same conclusion: that the addition of PlGF alone increases detection more than AFP alone, but the best performance is obtained with a four‐marker test and that this is comparable with a second‐trimester Quad test.…”
Section: Discussionmentioning
confidence: 85%
“…More recently, Bredaki et al . found a median of 0.71 MoM in 100 cases, and Donalson et al . reported 0.76 MoM in 92 cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The current DSS tests include the measurement of two maternal serum biomarkers in the first trimester (PAPP-A and free-beta-hCG) and four in the second trimester (alphafeto-protein (AFP), inhibin-A, oestriol and free-beta-hCG or total hCG). Recently it has been reported that the addition of other biomarkers, for example AFP and placental growth factor (PlGF) to the first trimester test has the potential to improve the detection of Down’s syndrome pregnancies and may also help identify pregnancies at high risk of other adverse pregnancy outcomes (preeclampsia and intra-uterine fetal growth restriction) [35,36]. As part of this study we will measure additional maternal serum biomarkers, including AFP and PIGF, in women undergoing DSS at a subset of participating hospitals.…”
Section: Introductionmentioning
confidence: 99%